2011
DOI: 10.1080/19440049.2011.604045
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the stability of antibiotics in matrix and reference solutions using a straightforward procedure applying mass spectrometric detection

Abstract: The stability of an antibiotic is a very important characteristic, especially in the field of antibiotic residue analysis. During method development or validation, the stability of the antibiotic has to be demonstrated no matter if the method is used for screening, confirmation, qualitative or quantitative analysis. A procedure for testing the stability of antibiotics in solutions and food samples using LC-MS/MS is described. The procedure is based on the assumption that the antibiotics are stable when stored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 10 publications
(3 reference statements)
1
42
0
Order By: Relevance
“…Very limited degradation was observed for all tested analytes during a storage period of 60 days (2 months) at −18 • C. The recovery ratio after and before storage was between 0.90 and 1.05 for all the veterinary drugs and pharmaceuticals, except for ampicillin which was subjected to a degradation of approximately 12%. These results come into agreement with previous published studies [46,[48][49][50]. Therefore, it was concluded that tissue samples that are kept frozen before analysis must be analyzed within the first 8 weeks of sample receipt.…”
Section: Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Very limited degradation was observed for all tested analytes during a storage period of 60 days (2 months) at −18 • C. The recovery ratio after and before storage was between 0.90 and 1.05 for all the veterinary drugs and pharmaceuticals, except for ampicillin which was subjected to a degradation of approximately 12%. These results come into agreement with previous published studies [46,[48][49][50]. Therefore, it was concluded that tissue samples that are kept frozen before analysis must be analyzed within the first 8 weeks of sample receipt.…”
Section: Stabilitysupporting
confidence: 92%
“…As it has been repeatedly reported in literature, these antibiotics show severe instability if stored for over than a 3-month period, even at −18 • C [2,46,47]. All other analytes present no degradation for at least 6 months when stored at −18 • C [2,[46][47][48][49][50]. Table S2.…”
Section: Chemicals and Reagentsmentioning
confidence: 82%
“…Many traditional antibiotics, including ␤-lactam antibiotics, cephalosporins, tetracyclines, and quinolones, are often unstable in aqueous solutions, which significantly restricts their usage (31,32). In contrast, Hc-CATH is extremely stable in aqueous solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study, examining the effect of sample storage at −18°C, showed that tetracyclines, sulfonamides, quinolones, macrolides, and aminoglycosides are stable and remain intact structurally and quantitatively, as demonstrated using a porcine muscle matrix [43]. However, penicillins were observed to attenuate, by about 30% and 20%, respectively, for ampicillin and cloxacillin over the course of 3-6 months [43]. Hence, the concentrations of penicillins at the time of purchase in samples of seafood analyzed here may have been higher than the values of less than <1.2 to <1.6 ng/g fw reported here.…”
Section: Resultsmentioning
confidence: 99%